The Development of Adobe Flash CS6-Based Interactive Media to Improve Numerical Literacy Skills for Madrasah Ibtidaiyah Students - Dian Septi Nur Afifah; Muhammad Ilman Nafi’an; Dinda Ayu Manggar (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
It is essential to improve students' numeracy literacy skills to apply concepts in everyday life and interpret information correctly, so interactive learning media is needed to support this. However, teachers need to be more optimal in using interactive learning media so that numeracy literacy skills are low. This study aimed to develop interactive media based on Adobe Flash Media CS6, the development used as ADDIE. The stages of this research model include Analysis, Design, Development, Implementation, and Evaluation. The results of this study indicate that the development of interactive learning media based on Adobe Flash CS6 can improve numeracy literacy skills. This can be seen from the average percentage of validity of 87% with very valid criteria, media expert validation of 78.3% with valid criteria, and practitioner validation of 94.2% with very valid criteria, besides that the average percentage of practicality obtained from the results of the black box testing questionnaire on five different types of android devices and types, 100% was successfully used. The percentage of effectiveness was 0.49, and the criteria were moderate. For this reason, interactive learning media based on Adobe Flash CS6 can be used as alternative learning at Madrasah Ibtidaiyah to improve numeracy literacy skills.Kemampuan literasi numerasi siswa penting untuk ditingkatkan agar siswa dapat mengaplikasikan konsep dalam kehidupan sehari-hari serta menginterpretasi informasi dengan baik, sehingga diperlukan media pembelajaran interaktif untuk mendukung hal tersebut. Namun guru belum maksimal dalam menggunakan media pembelajaran interaktif sehingga kemampuan literasi numerasi rendah. Tujuan penelitian ini adalah untuk mengembangkan media interaktif berbasis adobe media flash cs6, pengembangan yang digunakan adalah ADDIE. Adapun tahapan dari model penelitian ini meliputi: Analysis, Design, Development, Implementation, dan Evaluation. hasil dari penelitian ini menunjukkan bahwa pengembangan media pembelajaran interaktif berbasis adobe flash cs6 dapat meningkatkan kemampuan literasi numerasi. Hal ini dapat dilihat dari rata-rata persentase kevalidan sebesar 87% kriteria sangat valid, validasi ahli media sebesar 78,3% kriteria valid, dan validasi praktisi sebesar 94,2% dengan kriteria sangat valid, selain itu rata-rata persentase kepraktisan yang diperoleh dari hasil angket uji coba blackbox testing pada 5 perangkat android yang berbeda jenis dan tipe sebesar 100% berhasil digunakan dan persentase keefektivan sebesar 0,49 kriteria sedang. Untuk itu media pembelajaran interaktif berbasis adobe flash cs6 bisa digunakan alternatif pembelajaran di Madrasah Ibtidaiyah untuk meningkatkan kemampuan literasi numerasi.